A Uniquely British Indian Experience: Nitin Sawhney and Friends, BBC Prom 37. Royal Albert Hall, London, 10 August 2007 - Rachit Buch (Opticon1826, 2007)
This summer, British Indian artist Nitin Sawhney was granted the Royal Albert Hall for the occasion of BBC Prom 37, and gave an immensely accomplished performance. Sawhney, a veteran of seven studio albums and numerous live acts, represents the latest attempt by Prom director Nicholas Kenyon to reach a wider audience. The result was a multi-faceted musical evening, featuring orchestral film scores, Indian classical music instruments and dance. Although the addition of Zero Degrees’ choreographed narratives seemed to be a somewhat unnecessary addition, and the acoustics were not well suited for some of the pieces, the event proved to be a resounding success for Sawhney and the Proms.